The relationship between shyness, loneliness, and mobile phone addiction in Chinese university students: a cross-lagged analysis - Bai, Jing; Chen, Qi; Hu, Chang (Frontiers in Psychology, 2025)
PurposeGiven the increasing rates of mobile phone addiction (MPA) among university students, identifying the psychological processes that contribute to this phenomenon is of vital importance for prevention and intervention. This research employs a longitudinal approach to empirically investigate the causal relationships between shyness, loneliness, and mobile phone addiction in college students.MethodsFrom July 2024 to March 2025, a 9-month, three-wave longitudinal survey was conducted among 404 Chinese college students using the Cheek and Buss Shyness Scale, Emotional Versus Social Loneliness Scales, and the Mobile Phone Addiction Tendency Scale.Results(1) The synchronous and cross-lagged correlations among shyness, loneliness, and MPA were significant. (2) The direct predictive effect of shyness on MPA was found to be unstable, whereas MPA consistently predicted shyness. (3) Shyness consistently predicted loneliness, but the predictive effect of loneliness on shyness was found to be unstable. (4) Loneliness and MPA were found to be mutually predictive of each other. (5) T1 shyness significantly predicted T3 MPA through T2 loneliness; however, T3 MPA did not predict T3 shyness through T2 loneliness.ConclusionReducing shyness and loneliness can help alleviate MPA in college students, promoting their psychological and behavioral health. MPA may exacerbate loneliness and shyness, and early identification and intervention can help break this vicious cycle.